Sarcopenia: Body Composition and Gait Analysis - Fan, Yuxuan; Zhang, Bo; Huang, Guohao; Zhang, Guoying; Ding, Zhiyuan; Li, Zhiyu; Sinclair, Jonathan; Fan, Yifang (Frontiers in Aging Neuroscience, 2022)
Background: Age-induced sarcopenia negatively affects walking stability and increases the risk of falls, which represents the leading cause of accidental death in elderly. Objective: This study aimed to analyze and contrast body composition and gait characteristics in those with sarcopenia in relation to health controls in order to shed some light on the prevention of falls in elderly patients with sarcopenia. Materials and Methods: Sixty-eight community dwellers were scanned by Hologic QDR-4500A Dual-energy X-ray absorptiometry (DXA). The appendicular lean mass index (ALMI) results were used to distinguish the normal participants from those with sarcopenia: 24 in sarcopenia group, and 44 into normal group. The participants were asked to undergo gait analysis on a plantar pressure measurement system. Statistical analysis was conducted to contrast both groups’ gait and butterfly parameters from their gait test, and then a gait forward dynamics method was performed to quantify the analysis to both groups. Results: ALMI of the female was not related to their age (r=0.06) while that of the male was weakly related (r=0.17). Body mass index (BMI) from both groups was normal, although with a statistically greater BMI from the normal group compared to sarcopenia (p<0.001). Greater values and significant differences were found in step length and stride length from normal elderly group (p<0.01), and so were the length of gait line and single support line (p<0.05). Gait forward dynamics analysis results showed no motor neural or musculoskeletal disorders in their gait performance from sarcopenia group. Conclusion: For the elderly, age did not largely affect ALMI, BMI or T-score, but BMI and ALMI were strongly correlated. In this study, significant differences were found in certain gait parameters between the elderly with sarcopenia and the normal elderly, which were related to absolute muscle strength, suggesting that sarcopenia was a disease mainly caused by decreased muscle mass. In addition, when abnormities were identified in step length, stride length, length of gait line or length of single support line, it is proposed to take a DXA scan to confirm whether the elderly suffers from sarcopenia.